Functional iron deficiency and outcomes in patients with kidney disease - Hannah O’Keeffe; Firas AlTheyaib; Isabelle Newman; Sharmilee Rengarajan; Samira Lakhal-Littleton; Ivona Baricevic-Jones; Rajkumar Chinnadurai; Philip A. Kalra (PLoS ONE, 2026)
Introduction This study assesses the impact of functional iron deficiency (FID) on outcomes, including all-cause mortality, hospitalizations and non-fatal cardiovascular events in patients with non-dialysis chronic kidney disease (CKD) and hemodialysis (HD). Methods In HD, absolute iron deficiency (AID) was defined as ferritin < 200 µg/L and TSAT (transferrin saturation) ≤ 20%, and FID ferritin ≥200 µg/L with TSAT ≤20%. In CKD, AID was ferritin < 100 µg/L and TSAT ≤ 20%, and FID ferritin ≥ 100 µg/L with TSAT ≤ 20%. Prevalent HD patients as of January 2012 and incident patients between January 2012 and December 2014 were included (n = 512) and followed to 31/12/2018 (median 36.5 months). CKD patients who received iron infusions between January 2017 and December 2019 were included (n = 831) and followed until 31/12/2023 (median 38.5 months). Results In the HD cohort, 71% of the FID patients were dead at the end of follow-up (vs No Iron Deficiency, NID: 52%, AID: 48%; p = 0.008). In the CKD cohort, 62% of the FID group died by the end of follow-up (vs AID: 49.5%, NID: 46.2%; p = 0.001). The hazard ratio for FID for all-cause mortality was 1.89 (p < 0.001) in HD and 1.48 (p < 0.001) in CKD. Multivariate analysis found FID was independently associated with all-cause mortality (HD HR:1.50, p = 0.015; CKD HR: 1.46, p = 0.017). Patients with FID on HD were more likely to be hospitalized (median episodes 2.5 FID vs 2 in AID and NID, p = 0.041; FID: 22.5 days vs AID: 10, NID:14 days, p = 0.019). Conclusion FID was associated with all-cause mortality in patients with non-dialysis CKD and HD, and with higher rates of hospitalization and prolonged length of stay in HD.